Photogenerated acyl/alkoxycarbonyl/carbamoyl radicals for sustainable synthesis. Issue 4 (29th January 2019) - Raviola, Carlotta; Protti, Stefano; Ravelli, Davide; Fagnoni, Maurizio
Abstract : Recent examples of sustainable acylations by photogenerated acyl/alkoxycarbonyl/carbamoyl radicals have been discussed in this article. Abstract : Acylation reactions are of crucial importance in synthesis since they provide access to ketones or related derivatives. The well known acylations of aromatics (the Friedel–Crafts reaction) or olefins are commonly carried out under harsh and/or non-sustainable conditions. An alternative approach consists in the use of acyl (or related) radicals as acylating agents. Recently, the photochemical approach has been proposed as a green route for the generation of acyl/alkoxycarbonyl/carbamoyl radicals and their application in synthesis due to the mildness of the conditions employed. The reactions are mostly carried out at room temperature by using inexpensive visible or solar light. This article offers an overview on the photochemical/photocatalyzed pathways that allow the introduction of the acyl group in aromatics, alkenes and alkynes.